The war in Burma 1943-1944 - Holland, James 1970- (Ladybird Books Ltd, 2023)
Why were British troops in Burma? What was The Defence of the Admin Box? How did the British defeat the Japanese troops? THE BURMA CAMPAIGN was one of the most prolonged campaigns in the South-East Asian theatre of war, but it was also one of the most dramatic. Against Japanese troops, and monsoon weather, the Allies finally prevailed, demonstrating to the world that the Axis powers could be defeated in the East
Keywords: Great Britain / Army / History / 20th century; Japan / Rikugun / History / 20th century; Great Britain / Army; Japan / Rikugun; World War, 1939-1945 / Campaigns / Burma; Military campaigns; Burma / History / 1824-1948; Burma